ORGANIZATIONAL CAPACITY OF THE COOPERATIVE, UMKM, INDUSTRY AND TRADE OFFICE OF SUKABUMI CITY IN THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) - Ranti Riani; Ike Rachmawati; Tuah Nur (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
In conducting the development of micro, small and medium enterprises, the Department of Cooperatives, MSMEs, Industry and Trade (Diskoperindag) of Sukabumi City has the role and authority to do so. However, in the implementation in the field, based on the results of the author's interview with the Head of the SME Division in carrying out these activities, Diskoperindag experienced several obstacles. This study uses the theory of Horton (2003) which has 5 dimensions, namely human resources, technological infrastructure and financial resources, management programs and processes, the last dimension of networks/relationships with other organizations and stakeholders. This research uses descriptive qualitative approach documentation. The results of the study show that the organizational capacity of Diskoperindag in developing MSMEs is not yet adequate, because it is not fully in accordance with the theory of organizational capacity from Horton, et al. Of the five dimensions, only the strategic leadership dimension is adequate. Meanwhile, the dimensions of human resources, infrastructure, technology and financial resources, program and process management and network/relationship dimensions with other organizations and stakeholders are inadequate.